دراسة عددية لثبات المنحدرات الرملية المحملة على سطحها و المدعمة بالأوتاد - توفيق فياض; مهند مهنا; محار رجب (Tishreen University, 2018)
تعد مسألة ثبات المنحدرات وتأمين استقرارها من المشاكل الجيوتكنيكية الأساسية نظراً للأضرار الكبيرة (المادية والمعنوية) المرتبطة بالانهيار. يهدف هذا البحث إلى دراسة تأثير وجود الأوتاد على استقرار المنحدر المحمل بحمولة أساس شريطي على سطحه , ودراسة البارامترات المؤثرة على الاستقرار] البعد عن قمة المنحدر(X) , التباعد بين الأوتاد (S) , طول الوتد L)) , بعد طرف الأساس الشريطي عن قمة المنحدر (b)[ . لقد تم إنجاز البحث على مرحلتين : في المرحلة الأولى تم تشكيل نموذج عددي لمنحدر رملي باستخدام (برنامج FLAC3D) و حساب هبوط الأساس الموجود على سطح المنحدر قبل التدعيم بالأوتاد وبعده, ومقارنة النتائج مع نتائج مخبرية مرجعية (حالة مرجعية) , حيث أعطت النتائج العددية تقارباً مقبولاً مع النتائج المخبرية. أما المرحلة الثانية فتناولت دراسة بارامترية لأهم العوامل المؤثرة على استقرار المنحدر المدعم مثل (طول الأوتاد , التباعد بين الأوتاد, بعدها عن قمة المنحدر و بعد الأساس عن طرف المنحدر), حيث أظهرت الدراسة البارامترية أن تنفيذ الأوتاد بالقرب من قمة المنحدر أكثر فعالية في التدعيم حيث لوحظ زيادة عامل استقرار المنحدر المحمل بازدياد قرب الأوتاد من القمة وأعظم قيمة لمعامل الأمان كانت عند النسبة X=0.7Lx , كما أن استقرار المنحدر يعتمد بشكل ملحوظ على طول الوتد حيث يزداد عامل استقرار المنحدر المحمل بزيادة طول الأوتاد حتى الوصول إلى طول حدي للأوتاد يساوي ارتفاع المنحدر. أظهرت الدراسة الحالية فعالية الأوتاد في زيادة قدرة التحمل الحدية مع زيادة بعد الحمولة عن طرف المنحدر ونلاحظ ثبات قدرة التحمل الحدية عند زيادة بعد الأساس عن طرف المنحدر لمسافة تزيد عن b=3B . من جهة أخرى ينخفض عامل الاستقرار بزيادة التباعد بين الأوتاد حيث يبدأ تأثير الأوتاد بالتلاشي تقريباً عند زيادة التباعد عن ستة أضعاف قطر الوتد في حالة المنحدرات المحملة على سطحها (UBCR<1.1). The problem of slope stability is considered as a main geotechnical problem due to the significant damage (material or moral) related to failure. This paper aims to study the influence of piles on the stability of slopes loaded with strip footing and investigating the parameters affected on stability (location of pile row relative to the slope crest X , piles spacing S , piles length L and edge distance of the footing b  ). This study has been realized in two phases :  the first phase consists in establishing a numerical model for sand slope by using finite element analyses program (FLAC3D) and determining the footing settlement at crest of slope before using piles and after reinforcing , after that  the numerical results is compared with the experimental ones (reference case ). A close agreement between experimental and numerical curves is noticed .The second phase deals with studying the influence of most important parameters such as ( piles length ,piles spacing, pile row location relative to the slope crest on stability and edge distance of the footing) on the slope stability. The results of parametric study have shown the piles installed near the slope crest is more efficient in reinforcing  where the safety factor is increased by reducing the distance between row of piles and slope crest and the greatest value for safety factor when X=0.7Lx . The currently study showed the efficiency of piles to increase the ultimate bearing capacity with increasing edge, after that at b=3B the increase in ultimate bearing capacity decreased.  Also the slope stability depends significantly on pile length and it increases even reaching the length equals the height of the slope. At other hand, the safety factor is reduced  by increasing the piles spacing, so that the efficiency of pile is disappeared when pile spacing equals to six times pile diameter(UBCR<1.1).